L’impact de la lecture sur l’amélioration des compétences de la production écrite Cas des apprenants de 2ème année secondaire Lycée BEN GROUN Ahmed/Omar à BEN S’ROUR M’sila - REGUIEGUE Amina (My University, 2019)
Summary: Reading is an activity that has several advantages. It plays a key role in language acquisition because it is through reading that the learner enriches his or her linguistic background and improves oral and written skills. In order to highlight the impact of reading on the improvement of the language skills of the learner, especially those of written production, we conducted an experiment with students of the second year of high school BEN GROUN Ahmed / Omar BEN SROUR. The aim is to show to what extent reading can be at the service of written production.
Keywords: Key words: reading - linguistic background- improvement-skills.